Zoning of infiltration areas using Schosinsky’s Soil Water Balance in La Balsa River Basin, Costa Rica - Ramirez-Granados Pablo (Geološki Anali Balkanskoga Poluostrva)
In Central America there is little information of water infiltration at the basin level, despite its importance for the design of appropriate conservation and restoration strategies. Thus, the aim of this study is to develop an example for how to use Schosinsky´s Soil Water Balance (SSWB) model ‐along with other variables‐as a more viable way to determine water infiltration zones at the basin level. Zones, in La Balsa River Basin (LBRB), were determined by overlaying information of basin slopes, existing land use, land cover and spatial distributed rainfall. Hydrophysical soil properties in each zone were obtained through field tests measurements and laboratory analyses of soil samples. Once the values of each zone were determined, SSWB model was applied to obtain a map of infiltration zones. Results indicate that rainfall is the most influential component in calculating SSWB, and its distribution and deposition on the ground as effective rainfall is related to soil exposure and land use characteristics. Soil properties control the behavior of water that enters the soil and replenishes groundwater. Infiltration values, obtained using the model are highly correlated to rainfall dynamics. It is concluded that SSWB model is an important tool for obtaining water infiltration estimates at the basin level, useful in those basins for which little information is available.